Presenting Interpretive Structural Model of Sustainable Development Based on Ibn Khaldun’s Viewpoint - Mahdi Abdolhamid (Ibn Haldun University, 2020)
This paper is written with the understanding of the need for sustainable development on the one hand and the necessity of presenting an indigenous model of sustainable development for developing countries, especially Islamic countries. Accordingly, the authors have chosen Ibn Khaldun's views as one of the most prominent Islamic scholars as a source of research while choosing a historical perspective that is a mixture of countries' culture and experience. The method of this study is mixed (qualitative-quantitative). In this way, the library method is used for data collection. The content analysis method was used to analyze the collected data. As a result, the ten components of Sustainable development-Asabiyyah, Emphasizing on temperament, Eliminating poverty and creating welfare, Good governance, Citizenship rights, Scientific growth, Justice, Rationality, Population growth rate, To be based on people were extracted from Ibn Khaldun's viewpoint. Afterwards, the researchers referred to 10 experts familiar with Ibn Khaldun's thought and confirmed the extracted components and obtained their views on the type of relationships between these components in the form of interpretive structural modeling. Finally, an interpretive structural model of sustainable development based on Ibn Khaldun's theories was presented which revealed that the three components- Asabiyyah, Emphasizing on temperament, and To be based on people- have the most impact on sustainable development.